Aberrantly Methylated DNA as a Biomarker in Breast Cancer. Issue 2 (April 2013) - Kristiansen, Søren; Jørgensen, Lars M.; Guldberg, Per; Sölétormos, György
Aberrant DNA hypermethylation at gene promoters is a frequent event in human breast cancer. Recent genome-wide studies have identified hundreds of genes that exhibit differential methylation between breast cancer cells and normal breast tissue. Due to the tumor-specific nature of DNA hypermethylation events, their use as tumor biomarkers is usually not hampered by analytical signals from normal cells, which is a general problem for existing protein tumor markers used for clinical assessment of breast cancer. There is accumulating evidence that DNA-methylation changes in breast cancer patients occur early during tumorigenesis. This may open up for effective screening, and analysis of blood or nipple aspirate may later help in diagnosing breast cancer. As a more detailed molecular characterization of different types of breast cancer becomes available, the ability to divide patients into subgroups based on DNA biomarkers may improve prognosis. Serial monitoring of DNA-methylation markers in blood during treatment may be useful, particularly when the cancer burden is below the detection level for standard imaging techniques. Overall, aberrant DNA methylation has a great potential as a versatile biomarker tool for screening, diagnosis, prognosis and monitoring of breast cancer. Standardization of methods and biomarker panels will be required to fully exploit this clinical potential.